Modeling Salmonella Typhimurium Inactivation in Dry-Fermented Sausages: Previous Habituation in the Food Matrix Undermines UV-C Decontamination Efficacy - Mutz, Yhan S.; Rosario, Denes K. A.; Bernardes, Patricia C.; Paschoalin, Vania M. F.; Conte-Junior, Carlos A. (Frontiers in Microbiology, 2020)
The effects of previous Salmonella Typhimurium habituation to an Italian-style salami concerning pathogen resistance against UV-C treatment were modelled in order to establish treatment feasibility for the decontamination of dry-fermented sausage. S. Typhimurium following 24h habituation in fermented sausage (habituated cells) or non-habituation (non-habituated cells) were exposed to increasing UV-C radiation treatment times. The Weibull model was the best fit for describing Salmonella UV-C inactivation. Heterogeneity in UV-C treatment susceptibilities within the S. Typhimurium population was observed, revealing intrinsic persistence in a sub-population. UV-C radiation up to 1.50J/cm2 was a feasible treatment for dry-fermented sausage decontamination, as the matrices retained instrumental color and lipid oxidation physiochemical characteristics. However, habituation in the sausage matrix led to a 14-fold increase in the UV-C dose required to achieve the first logarithm reduction (δ value) in Salmonella population. The results indicate that, although UV-C radiation might be considered an efficient method for dry-fermented sausage decontamination, effective doses should be reconsidered in order to reach desirable food safety parameters while preserving matrix quality.